Internet Addiction and Its Association With Sleep Problems Among Early Adolescents in a Peri-Urban Area - Aidza Ajrina Maharani; Farid Agung Rahmadi; Mulyono Mulyono; Widodo Sarjana AS (Diponegoro International Medical Journal, 2025)
Background: The use of the internet among adolescents increases rapidly, particularly since COVID-19 pandemic, due to the necessity of online learning. Excessive internet use may progress to internet addiction, which has been identified as a risk factor for sleep disturbances. Sleep disorders that occur in adolescents may persist into adulthood, can result in sustained detrimental effects on health, especially in individuals aged 10-12 years, as they are still on critical period of growth and neurodevelopment. Data from Demak show that 30% from 40,000 students from elementary to high school have been addicted to online games, which represents a major subtype of internet addiction. Objective: To determine the relationship between internet addiction and sleep disorders among adolescents aged 10-12 years. Methods: A cross-sectional, analytical observational study was conducted. Data were obtained using the Internet Addiction Diagnostic Questionnaire questionnaire and the Sleep Disturbance Scale for Children (SDSC) questionnaire, administered to four grades and five grades at Bintoro 5 Elementary School in Demak, recruited through purposive sampling. Statistical analysis was performed using chi-square tests and multivariate logistic regression to control the confounding variables such as physical activity, obesity, and co-sleeping. Results: Among 81 respondents, the prevalence of internet addiction was 35.8% (n=29), and the prevalence of sleep disorders was 61.7% (n=50). Bivariate analysis using chi-square test demonstrated a significant relationship between internet addiction and sleep disorders P<0.05 (0.008). After controlling for confounding factors with logistic regression, the result remained statistically significant P<0.05 (0.006). Conclusion:Internet addiction is significantly associated with sleep disorders in adolescents aged 10-12 years, even after controlling for confounding factors.